Enhancing Customer Satisfaction Through Optimized Fast Track Lines: A Case Study Of Pertamina Fuel Stations - Aditya, Aria; Windasari, Nila Armelia; Mussry , Jacob Silas (Riviera Publishing, 2025)
The Fast Track Special Lane at Pertamina gas stations is a form of service innovation that aims to improve operational efficiency and customer satisfaction. The implementation of this service still has several obstacles, especially related to the lack of clarity of the difference between the Fast Track lane and the regular lane, as well as the mismatch between customer expectations and the real experience they feel. This reduces the effectiveness of the service, so a strategic approach is needed to improve the performance of the service. This study aims to identify the most effective strategy in managing the Fast Track Special Lane in order to increase the level of user satisfaction. This study uses a qualitative and quantitative Mix method. In the quantitative method, the analysis is carried out by calculating the Customer Satisfaction Score (CSAT) based on data from 150 respondents who have used this service. While the qualitative approach is carried out through in-depth interviews with consumers and gas station managers, as well as direct observation in the field. Qualitative data is analyzed using NVivo software to find patterns and main themes related to the effectiveness of the Fast Track service. This study aims to find out (1) How does Pertamina create a clear distinction between the Fast Track Lane and the regular lane so that the quality of service and value received by customers increases? (2) What are customers' expectations of this service, and how can this feedback be used to improve their experience and increase their satisfaction levels?By integrating quantitative and qualitative analysis, this research is expected to provide strategic recommendations for Pertamina in optimizing the management of Special Fast Track Lines, ultimately leading to enhanced customer satisfaction and a more competitive positioning in the premium fuel segment.